2022
DOI: 10.3390/jpm12121981
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Management in Neurology: Time for Revised Strategies?

Abstract: Statin therapy has been extensively evaluated and shown to reduce the incidence of new or recurrent vascular events, ischemic stroke included. As a consequence, each published guideline pushes for lower low-density cholesterol levels in the population at large, recommending increased statin doses and/or adding new cholesterol-lowering molecules. Neurologists find it sometimes difficult to apply these guidelines, having to confront situations such as (1) ischemic strokes, mainly cardioembolic ones, in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 162 publications
0
2
0
Order By: Relevance
“…In regard to antioxidative therapy, statins have been proposed to be valuable in improving neurocognitive disorders including both dementia and postoperative delirium, due to its ability to reduce the levels of oxidative species [38,39]. Although currently there are no clinical studies underway to investigate this favourable result of statins, previous randomized controlled trials demonstrated a significant reduction on early postoperative memory impairment by using statin therapy [39,40].…”
Section: Therapeutic Interventions: From Experimental To Clinical Fin...mentioning
confidence: 99%
“…In regard to antioxidative therapy, statins have been proposed to be valuable in improving neurocognitive disorders including both dementia and postoperative delirium, due to its ability to reduce the levels of oxidative species [38,39]. Although currently there are no clinical studies underway to investigate this favourable result of statins, previous randomized controlled trials demonstrated a significant reduction on early postoperative memory impairment by using statin therapy [39,40].…”
Section: Therapeutic Interventions: From Experimental To Clinical Fin...mentioning
confidence: 99%
“…In an experimental setting, DJ-1 knockdown exacerbated rotenone-induced impairments of mitochondrial fission [187], led to increased nitrative stress [188], and to increased production of COX-2 and IL-6 after LPS treatment [189]. DJ-1 also associates with lipid rafts [190], cholesterol-enriched membrane domains with a crucial role in synaptic transmission, endoand exocytosis, as well as signal transduction [191]. The astrocytic dysregulation of the inflammatory response appears to be related to TLR4 receptors, DJ-1 knockout astrocytes having impaired lipid raft assembly leading to impaired TLR4 endocytosis [192].…”
Section: Dj-1 and Parkinson's Diseasementioning
confidence: 99%